2017
DOI: 10.1073/pnas.1618364114
|View full text |Cite
|
Sign up to set email alerts
|

Modification of host dendritic cells by microchimerism-derived extracellular vesicles generates split tolerance

Abstract: Maternal microchimerism (MMc) has been associated with development of allospecific transplant tolerance, antitumor immunity, and cross-generational reproductive fitness, but its mode of action is unknown. We found in a murine model that MMc caused exposure to the noninherited maternal antigens in all offspring, but in some, MMc magnitude was enough to cause membrane alloantigen acquisition (mAAQ; "cross-dressing") of host dendritic cells (DCs). Extracellular vesicle (EV)-enriched serum fractions from mAAQ + , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 41 publications
4
97
0
Order By: Relevance
“…The natural consequences of durable tolerance to NIMA on reproduction remain incompletely understood. However, tolerance to NIMA has been shown to be relevant to transplantation outcomes [23,24], dependent on persistence of MMc in offspring [12] and possibly related to MMc-derived extracellular vesicles [25], and likely relevant to next-generation pregnancy outcomes [26]. …”
Section: Mmc: Shaping the Immune System Beginning In Fetal Lifementioning
confidence: 99%
“…The natural consequences of durable tolerance to NIMA on reproduction remain incompletely understood. However, tolerance to NIMA has been shown to be relevant to transplantation outcomes [23,24], dependent on persistence of MMc in offspring [12] and possibly related to MMc-derived extracellular vesicles [25], and likely relevant to next-generation pregnancy outcomes [26]. …”
Section: Mmc: Shaping the Immune System Beginning In Fetal Lifementioning
confidence: 99%
“…When the backcross breeding was done in such a way that maternal cells could be tagged by GFP, we found that higher levels of MMc were associated with 1) tolerance to a subsequent DBA-2 heart allograft; 2) the presence of immune regulatory cells specific for the NIMA d Ag in spleen and lymph nodes; and 3) the presence of GFP + maternal cells in CD11b + and CD11c + myeloid cell populations [45]. Since CD11c + DCs are also known to be capable of secreting large numbers of EVs/exosomes, we tested whether the serum of the offspring contained MHC Ags in the form of EVs [46]. We found that we could divide the NIMA d -exposed offspring into 2 types – one type, with low levels of MMc, had no membrane-bound alloantigen acquired on the surface of their mDCs (hereafter referred to as “non-mAAQ” mice).…”
Section: Exosome Transfer and Split-tolerance To Non-inherited Maternmentioning
confidence: 99%
“…In mice with membrane alloantigen acquisition (mAAQ + ), by contrast, the IE molecule was present both in the EV-free serum fraction and the ultracentrifuge pellet containing EVs. Analyses of EV-enriched fractions showed the presence of exosome-sized vesicles (50–110 nm diameter), enriched for the exosome marker CD9, with low content of Golgi, endoplasmic reticulum, and histone proteins [46]. Furthermore, when EVs from the mAAQ + serum were tested in a short-term culture with B6 (H2 d-negative ) cells, both plasmacytoid DCs (pDCs) and mDCs were found to acquire surface H2-K d (MHC class-I) and IA d (MHC class-II) molecules of maternal origin.…”
Section: Exosome Transfer and Split-tolerance To Non-inherited Maternmentioning
confidence: 99%
See 1 more Smart Citation
“…The recipient APCs cross-dressed with donor–derived exosomes stimulate proliferation and terminal differentiation of directly allo-reactive T cells through the semi-direct pathway of allo-recognition 4,5 . Transfer via exosomes of noninherited maternal MHC allo-Ag (NIMAs) from maternal microchimeric cells to host APCs is behind the T cell split tolerance against NIMAs 6 .…”
mentioning
confidence: 99%